1998
DOI: 10.1152/ajpendo.1998.275.6.e993
|View full text |Cite
|
Sign up to set email alerts
|

Insulinotropic action of β-l-glucose pentaacetate

Abstract: The metabolism of β-l-glucose pentaacetate and its interference with the catabolism ofl-[U-14C]glutamine, [U-14C]palmitate,d-[U-14C]glucose, andd-[5-3H]glucose were examined in rat pancreatic islets. Likewise, attention was paid to the effects of this ester on the biosynthesis of islet peptides, the release of insulin from incubated or perifused islets, the functional behavior of individual B cells examined in a reverse hemolytic plaque assay of insulin secretion, adenylate cyclase activity in a membrane-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[39] high-fat diet-fed mice mouse Supplementation of luteolin in diet promoted thermogenesis in BAT and subcutaneous adipose tissue. [40] primary adipocytes human Silibinin increases thermogenic marker genes [41] Liver high-fat diet-fed mice mouse Supplementation of oleuropein to diet reduced liver weight and hepatic triglyceride level [47] diet-induced obese mice mouse Oral gavage of KDT501 reduced lipid deposition of the liver [48] high-fat diet-fed mice mouse Supplementation of epigallocatechin-3-gallate to diet reduced hepatic lipid and cholesterol content [49] Islet HIT-T15 cells isolated islet hamster rat Denatonium benzoate induces insulin secretion [50] isolated islet rat β-L-Glucose pentaacetate induces insulin secretion [51]…”
Section: Nci-h716cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] high-fat diet-fed mice mouse Supplementation of luteolin in diet promoted thermogenesis in BAT and subcutaneous adipose tissue. [40] primary adipocytes human Silibinin increases thermogenic marker genes [41] Liver high-fat diet-fed mice mouse Supplementation of oleuropein to diet reduced liver weight and hepatic triglyceride level [47] diet-induced obese mice mouse Oral gavage of KDT501 reduced lipid deposition of the liver [48] high-fat diet-fed mice mouse Supplementation of epigallocatechin-3-gallate to diet reduced hepatic lipid and cholesterol content [49] Islet HIT-T15 cells isolated islet hamster rat Denatonium benzoate induces insulin secretion [50] isolated islet rat β-L-Glucose pentaacetate induces insulin secretion [51]…”
Section: Nci-h716cellsmentioning
confidence: 99%
“…The GTEx database also shows that TAS2R3, 4, 5, 10, 14, 19, 20, and 31 are expressed in the pancreas (Figure 1); however, the role of T2Rs in the pancreas has not been carefully studied. Nonetheless, some bitter compounds have been reported to induce insulin secretion in isolated pancreatic islets, including denatonium benzoate and β-L-glucose pentaacetate [50,51]. One study showed that the effect of denatonium benzoate on insulin secretion was apparently mediated by a transducin-independent pathway, involving a decrease in ATP-sensitive potassium (KATP) channel activity, depolarization of β-cells, and increased Ca 2+ influx [50], casting doubt on the involvement of T2Rs.…”
Section: Pancreatic Isletsmentioning
confidence: 99%